Pengaruh Kinerja Sumber Daya Manusia Terhadap Kredibilitas Perusahaan: Sebuah Tinjauan Literatur Sistematis : The Effect Of Human Resource Performance On Company Credibility: A Systemic Literature Review - Muhammad Amirul Huda; Riyan Sisiawan Putra (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2022)
There are many things that need to be considered in order to be as expected. In the field of management itself, it does not always discuss the calculation but also discusses the system and human resources. In a company, where human resources (HR) can develop and participate in developing the company so that it has a good image in the community. This then makes a company more selective in the process of recruiting employees and experts in their fields to be able to work in the company. Because quality human resources (HR) will make it easier for a company to develop and make it easier for these HR to develop and advance within the company. This paper describes descriptive analysis and content analysis by examining 100 journal sources that are analyzed in a structured manner in human resource management in a company. From several journals that have been analyzed previously, the results show that the level of quality HR greatly affects the performance of a company itself. In this analysis, a good company and has a good image both for the community and for its employees can trigger the HR in it to work more professionally in their fields. In addition, this paper contains an analysis of previous journals where in each discussion of the contents of the journal there are several in the writing process that are felt to be lacking and also the discussion is less thorough. It is hoped that in the future researchers with similar topics will explore more information and literature to facilitate the process of making research results.